Aplikasi NodeMCU ESP8266 Untuk Monitoring Kelembaban Tanah Berbasis Internet of Things - Sarwansah, Rivan; Jaelani, Usman; Hasad, Andi; Supratno, Setyo; Sugeng, Sugeng (Journal of Students‘ Research in Computer Science, 2022)
In today's modern era, the use of the Internet of Things (IoT) has been widely applied in various fields, almost all electronic devices are connected to the internet. Along with the development of technology, the application of technology in agriculture is very important. Due to the increasing need for plant monitoring and care. Therefore, the importance of plant care and monitoring so that the plants planted can produce good quality. In this research, an automatic plant watering and monitoring system is designed that is connected to the internet network so that users can care for and monitor plants so that they are maintained and produce quality plants. This system is designed using NodeMCU ESP8266 microcontroller as the system control center. In this study, a system for monitoring and watering plants automatically has been successfully designed by reading the moisture content in the soil. The result is that this system can provide the right water requirements for plants. Then the system sends information to the website page that has been built so that users can monitor the plants.